(untitled) (Community Based Medical Journal, 2026)
Forensic Medicine & Toxicology in MBBS curriculum tends to produce a physician who will be well informed and alerts about his/her medico-legal responsibilities and is capable of being discharging medico-legal duties in medical practice. Integrated teaching and learning aims to provide better deliverables, better understanding and more student engagement. In undergraduate medical education in Bangladesh, the term ‘integrated teaching’ has become familiar among medical teachers and students just over a decade; however, not all medical colleges have resources, expertise and practice of integrated teaching in their instructions. Transformation towards integrated teaching involving teachers of different disciplines to teach common topics in Forensic Medicine & Toxicology aims to develop creativity, critical and logical thinking, practical learning, extended retention of knowledge and research aptitude as well as ethics and professionalism among the students. Through student-centric pedagogy, our integrated teaching approach is expected to be more helpful in reducing the theoretical and practical gap in Forensic Medicine & Toxicology education under MBBS curriculum. Besides, such teaching approach will open new avenues of research in medical education including further curriculum designing and revisiting assessment procedures, which will result in a paradigm shift. In this review paper, we will discuss regarding integrated teaching in Forensic Medicine & Toxicology curriculum in undergraduate medical education focusing on how to integrate interdisciplinary approach, ‘SPICES’ teaching model and benefits as well as challenges encountered during its implementation. CBMJ 2026 January: vol. 15 no. 01 P:260-267